Suatu Kajian Tentang Grup Fuzzy - Muhammad Abdy; Sukarna; Rahmah Abubakar (Journal of Mathematics, Computations and Statistics, 2018)
This research aims to review the basic concept of fuzzy group from classic group that have been introduced by Azriel Rosenfeld, and in addition,to find the connection between the properties of classic group and properties of fuzzy group. Show that the Theorem 7 is can't be applied in fuzzy group.